Empowering coastal women through marine resource innovation: Transforming low-value catch into standardized processed products - Ikha Safitri; Warsidah Warsidah; Apriansyah Apriansyah; Mega Sari Juane Sofiana; Tia Nuraya; Sukal Minsas; Arie Antasari Kushadiwijayanto; Syarif Irwan Nurdiansyah; Yusuf Arief Nurrahman; Iwan Kuncoro; Alvianita Rika Putri Kusumaningsih; Nimaz Tegar Sukma; Dwi Imam Prayitno; Shifa Helena; Nora Idiawati; Harianto Harianto; Surya Darma (Community Empowerment, 2026)
Kuala Secapah Village serves as a prominent hub for capture fisheries along the coast of West Kalimantan. Alongside premium catches, local fishermen frequently haul trash fish (ikan rucah), that remains economically underutilized. Applying innovative and sustainable processing approaches to these marine resources can significantly generate added value for the community. This community service program aims to educate and train coastal women on upgrading these underutilized catches into competitive food products. The program was delivered in participatory workshop divided into two sessions: an instructional lecture and a hands-on culinary production practice. The intervention yielded substantial progress, with participants' technical knowledge skyrocketing from 64% to 99.6% regarding standardized and proper fish-processing techniques. Ultimately, this initiative successfully fosters local economic resilience by converting underutilized marine waste into high-value commodities.